الاستثناء في قانون ضريبة الدخل العراقي: دراسة مقارنة - د. قبس حسن عواد البدراني (PROSPECTIVE RESEARCHES, 2023)
The present research tackles the legal principles of tax legislation, viz. tax exception. Tax exception is not considered an outlaw act, but it is in the range of legality. This is why it is necessary to emphasize the importance of investigating that exception identifying its main principles and legal evidence. After that, it has been compared to the Egyptian law. It has been discovered that this exception is comprehensive involving many legal texts in both the Iraqi and Egyptian laws. The study concludes that this exception is an essential stable procedure in tax regulations when putting legislation about tax to get out of the total basics regulations to apply it for the sake of public interest which may be changed from time to time.